Importance of Teaching Vocabulary: The Whys and Hows ("Conference on Universal Science Research 2023", 2023)
This article focuses on providing teachers with the whys and hows to implement tier-two vocabulary instruction in PK-12 grade classrooms. The article examines what is meant by tier-two vocabulary words and the need for increased vocabulary instruction to gain word knowledge. It also offers teachers applicable texts and activities to be used when they become teachers and ways to incorporate a school- to-home connection in support of students' learning of new vocabulary words. The texts and activities are divided into three grade levels: K-2, 3-5, and 6-12. In addition, the article is divided into two sections, which outlines the whys and hows for increasing students' vocabulary knowledge.